An analysis of selling concessions, reallowance fees, and price changes in the marketing of IPOs - James C. Brau; Joseph J. Henry (The Journal of Entrepreneurial Finance (JEF), 2022)
This paper provides an economic model resulting in two distinct marketing strategies available to investment bankers. First, we hypothesize that an increased selling effort by brokers is used most effectively when the investment clientele is uninformed. Second, adjusting the offer price of the issue is hypothesized to be employed primarily in large IPOs with a clientele of sophisticated investors, consistent with Shiller's Impresario Hypothesis. Our pre-IPO bubble (1981-1996) empirical results yield evidence supporting both selling mechanisms. Under-demanded small IPO issues are "pushed" by the brokers, while some under-demanded large IPO issues instead increase the offer price, with large first-day turnover characteristics of flipping. Both types of issues experience large and significant negative long-term returns, as share prices eventually return to the equilibrium price. For the post-IPO bubble period (1997-2017), the Impresario Hypothesis is empirically supported, but the push strategy is not, indicating a partial shift in selling mechanisms post bubble.
Keywords: G24; G30; G32; G40; 650; Initial Public Offering; IPO; Selling Strategies; Underpricing